Guidance and Counseling on Learning Media Innovations For Middle School Teachers at the Telukjambe Karawang Commissariat: Bimbingan dan Penyuluhan Inovasi Media Pembelajaran Untuk Guru-Guru SMP Se-Komisariat Telukjambe Karawang - Sutirna Sutirna; Suntoko Suntoko; Yayah Nurasiah; Umar Mukhtar; Beben Zuber Effendi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Because technological developments are increasing on a daily, the purpose of this service is to inform about the importance of innovating in information technology-based learning and evaluation. The service method uses a workshop for teachers of public and private middle schools throughout the Telukjambe Karawang Commissariat Area, which is framed in a guidance and counseling activity on learning media. A perception questionnaire about the teacher's interest in developing internet-based learning media is used as the instrument. The results of this dedication found that teachers were so very high to innovate in the learning process and evaluation of learning. but, on average, convey the same perception constraints, Namely, there is a lack of facilities and infrastructure for conducting internet-based learning and evaluation, the internet network has not been evenly distributed to school locations in the regions, and school principals is support and low motivation of providing internet facilities.